2020
DOI: 10.1021/acs.orglett.0c02770
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Photocatalytic Synthesis of Guanidine from Thiourea under Visible Light

Abstract: In this work, we developed the catalytic guanylation of thiourea using Ru(bpy) 3 Cl 2 as a photocatalyst under irradiation by visible light. The conversion of various thioureas to the corresponding guanidines was achieved using 1−5 mol % of photocatalyst in a mixture of water and ethanol at room temperature. Key benefits of this reaction include the use of photoredox catalyst, low-toxicity solvents/base, ambient temperature, and an open-flask environment.The Supporting Information is available free of charge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
4
15
0
Order By: Relevance
“… 24 These results indicated that the reactive oxygen species might be ground-state oxygen ( 3 O 2 ), however, a minor contribution from other active oxygen species could not be completely excluded. Based on the mechanistic studies and previous reports, 19,24 a although the mechanism of this visible-light-catalyzed guanylation reaction was not unequivocally demonstrated, a reasonable possibility is outlined in Scheme 2e . The tautomer I of diphenylthiourea is transformed into a radical intermediate II through a proton-coupled electron transfer (PCET) to the excited state catalyst DP4*.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“… 24 These results indicated that the reactive oxygen species might be ground-state oxygen ( 3 O 2 ), however, a minor contribution from other active oxygen species could not be completely excluded. Based on the mechanistic studies and previous reports, 19,24 a although the mechanism of this visible-light-catalyzed guanylation reaction was not unequivocally demonstrated, a reasonable possibility is outlined in Scheme 2e . The tautomer I of diphenylthiourea is transformed into a radical intermediate II through a proton-coupled electron transfer (PCET) to the excited state catalyst DP4*.…”
Section: Resultsmentioning
confidence: 95%
“…Very recently, Wacharasindhu's group reported the first photocatalytic process for guanylation of thioureas under visible light. 19 They screened the common visible-light organic PCs including eosin Y, rose bengal, and safranin O, as well as a transition-metal photoredox catalyst Ru(bpy) 3 Cl 2 . Among them, only Ru(bpy) 3 Cl 2 showed good catalytic activity and enabled the guanylation of diaryl thioureas with 1° and 2°-alkyl amines in high yields ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thiyl radical, upon addition to the alkyne, gives vinyl radical 1c , which undergoes hydroperoxide insertion to afford peroxy intermediate 1d . In another parallel photocatalytic cycle (PC-2), the thiol tautomer of thiourea engages in single electron transfer to Ru 2+* (SET), generating thiyl radical cation 1e , which after deprotonation affords intermediate 1f and Ru 1+ . The thiol radical 1f attacks intermediate 1d , which undergoes facile peroxide cleavage, generating intermediate 1g and a hydroxyl radical .…”
mentioning
confidence: 99%